The New Democracy: Challenging the Social Order in Industrial Ontario, 1914-1925 - Naylor, James (University of Toronto Press, 1991)
James Naylor traces the transformation of class relations in the industrial cities of southern Ontario, examining the character of the regional labour movement, the nature of employer and state response, and the reasons for the failure of labour's "new democracy." --Publisher's description. Inside front-cover summary: The period during and after the First World War was marked by tremendous labour unrest, not only in Winnipeg where the general strike of 1919 was a watershed, but across the country. James Naylor focuses on southern Ontario, in the industrial heartland of Canada, as a key to understanding the character of this phase of labour history. In the 1919 provincial election, the Independent Labor Party of Ontario swept most of the province's industrial constituencies outside Toronto and formed a coalition government with the organized farmer. Strike activity soared to unprecedented levels. The Toronto Trades Council organized a general strike, and new forms of industrial unionism began to emerge. If these events lacked some of the drama of those in the West, they reflect both an increasingly articulate working-class view of democracy and labour's determination not to be overlooked in the postwar reconstruction. Naylor examines a number of issues: the nature of working-class views of democracy and the state; the role of women in these movements; the logic participation in the electoral process; the dynamic between 'industrial' and 'political' activity in the context of a liberal-democratic system. He also considers the responses of employers and government with a view to undertanding the 'negotiated' character of postwar reconstruction in the context of social classes.
Keywords: Arbeidersbeweging; Electronic books; HISTORY Canada General; History; Livres numériques; Ontario; Politieke participatie; SOCIAL SCIENCE Discrimination & Race Relations; SOCIAL SCIENCE Minority Studies; Travailleurs Ontario Histoire; Working class; Working class Ontario History; e-books